(untitled) (International conference on multidisciplinary science, 2024)
Over the past few decades, the concepts of the biological basis for the development of ventral hernias, surgical techniques and the use of biomaterials for abdominal wall plasty have significantly expanded. Biomaterials significantly improved the postoperative course with a significant reduction in the recurrence rate from 50% to less than 20%. However, there are different opinions in this regard. Despite the fact that it has been proven that prosthetic allogernioplasty led to a decrease in the frequency of relapses, the negative aspect of this type of surgery was a higher risk of developing wound complications compared with restoration with local tissues only.